2016
DOI: 10.1093/jjco/hyw004
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ghrelin levels as a predictor of adverse renal events due to cisplatin-based chemotherapy in patients with esophageal cancer

Abstract: Objective: Although combination chemotherapy with docetaxel, cisplatin and 5-fluorouracil demonstrates high response rates in esophageal squamous cell carcinoma, patients treated with docetaxel, cisplatin and 5-fluorouracil frequently experience acute kidney injury. Ghrelin has shown renal protective effects in an experimental acute kidney injury model by reducing tubular apoptosis. In this prospective observational study, we evaluated the association between plasma ghrelin concentrations and docetaxel, cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In this study, DOX significantly decreased the circulating plasma levels of AG, increased those of DAG and reduced the overall ratio of AG/DAG. A similar picture was also seen in patients with renal failure or cancer patients after chemotherapy with cisplatin 37,40,42 . Some authors have attributed such an increase in DAG to the concurrent decrease in its clearance due to the associated renal damage 40 .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In this study, DOX significantly decreased the circulating plasma levels of AG, increased those of DAG and reduced the overall ratio of AG/DAG. A similar picture was also seen in patients with renal failure or cancer patients after chemotherapy with cisplatin 37,40,42 . Some authors have attributed such an increase in DAG to the concurrent decrease in its clearance due to the associated renal damage 40 .…”
Section: Discussionmentioning
confidence: 53%
“…Of note, levels of AG and DAG are significantly increased during AKI and renal failure 28,40 . However, serum AG levels are significantly decreased in patients (by 60%) after cisplatin and DOX‐based chemotherapy and were strongly correlated with the degree of renal dysfunction 37,41,42 . However, in a randomized phase II trial of cisplatin‐treated cancer patients, continuous administration of AG attenuated renal dysfunction, thus suggesting that AG is an interesting option to prevent chemotherapy‐induced renal damage 37 …”
Section: Introductionmentioning
confidence: 99%
“…These results suggest the molecular mechanisms underlying the renal protective effect of ghrelin against cisplatin-induced nephrotoxicity. In fact, our previous study showed that blood ghrelin concentrations are decreased to ∼60% of pre-chemotherapy levels early in the course of cisplatin-based chemotherapy, and that lower plasma acyl ghrelin levels are associated with renal dysfunction during cisplatin-based chemotherapy ( Yamamoto et al , 2013 ; Yanagimoto et al , 2016 ). Thus, we conducted this prospective interventional trial of ghrelin to test the hypothesis that it decreases the renal dysfunction induced by cisplatin nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our previous study, we estimated that the mean serum creatinine in the placebo group would be 1.1±0.3 mg dl −1 ( Yanagimoto et al , 2016 ). The sample size calculation was based on a 20% improvement by ghrelin administration, power of 80% and alpha of 10%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation